Eco-Friendly Synthesis of Zinc Oxide Using Green Alkaline Solution for Enhanced Solar-Driven Photocatalytic Degradation of Methylene Blue - Abbes, Nedra; Fridjine, Sana; Barhoumi, Thouraya; Sejri, Nejib; Jaouachi, Boubaker; Xu, Jun; Abbes, Imene Bekri (Indonesian Journal of Chemistry, 2026)
Zinc oxide (ZnO) particles were green-synthesized using an aqueous extract of olive wood ash as a sustainable alkaline precipitating agent. The extract pH stabilized near 13 (40 wt.%), confirming strong alkalinity. A two-step process involved forming a zinc carbonate precursor, followed by calcination at 900 °C. X-ray diffraction confirmed highly crystalline hexagonal wurtzite ZnO. Optical analysis revealed a reduced bandgap of 2.80 eV, significantly lower than the conventional value of 3.37 eV, attributed to lattice defects and elemental incorporation. Evaluating the photocatalytic efficiency against methylene blue under natural solar light, the green-synthesized ZnO achieved nearly 99% removal within 2 h, outperforming conventional ZnO due to enhanced solar absorption from its narrowed bandgap. This work validates a zero-waste pathway for synthesizing highly active nanomaterials, setting a strong precedent for circular economy applications in sustainable photocatalysis.